Terapi dengan aroma lavender pada gangguan pola tidur lansia di Desa Sukajaya Lempasing Pesawaran - Sumo, Ni Luh; Furqoni, Prima Dian; Elliya, Rahma (JOURNAL of Public Health Concerns, 2025)
Background: The aging process in older adults (60 years and older) reduces biological, psychological, and social functioning, increasing susceptibility to infection, cognitive impairment, and disrupted sleep patterns, which negatively impact quality of life. In Lampung Province, 70% of social care residents reported difficulty initiating and maintaining sleep. Although sleeping pills are effective in the short term, the risk of dependency and side effects encourage the use of non-pharmacological interventions. Lavender aromatherapy, with its antiseptic and relaxing properties, has been shown to be effective in reducing the severity of insomnia in older adults. A pre-survey in Sukajaya Lempasing Village confirmed that 70% of older adults experience sleep disorders, underscoring the need for integrated interventions to improve sleep quality and quantity. Purpose: To provide an overview of nursing care using lavender aromatherapy interventions for older adults experiencing sleep disorders. Method: The study was conducted from June 26 to July 3, 2025, in Sukajaya Lempasing Village, Pesawaran, Lampung. Two elderly individuals were selected as respondents based on inclusion and exclusion criteria. The lavender aromatherapy intervention was administered for seven days, accompanied by family support, and face-to-face meetings on the first and eighth days. The study used a one-group pre-test and post-test design. Data were collected through assessments, interviews, and observations using observation sheets and the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed descriptively to compare pre- and post-intervention scores. Results: The lavender aromatherapy intervention demonstrated improved sleep quality in both respondents, with a decrease in sleep disturbance scores from poor to good: Respondent 1 decreased from 17 to 7, and Respondent 2 decreased from 16 to 6. Conclusion: Seven days of lavender aromatherapy proved effective as a non-pharmacological independent nursing intervention, resulting in a decrease in sleep disturbance scores in the elderly from poor to good, an increase in sleep duration to 6–7 hours per day, and improvements in symptoms and relaxation. Suggestion: Lavender aromatherapy should be integrated into nursing practice for older adults with sleep disorders through relaxation education, sleep environment management, regular monitoring, and family involvement for long-term effectiveness. Keywords: Elderly; Lavender aromatherapy; Sleep pattern disorders Pendahuluan: Proses penuaan pada lansia (≥ 60 tahun) menurunkan fungsi biologis, psikologis, dan sosial, sehingga meningkatkan kerentanan terhadap infeksi, gangguan kognitif, dan gangguan pola tidur yang berdampak negatif pada kualitas hidup. Di Provinsi Lampung, 70% penghuni panti sosial melaporkan kesulitan memulai dan mempertahankan tidur. Meski obat tidur efektif jangka pendek, risiko ketergantungan dan efek samping mendorong penggunaan intervensi nonfarmakologis. Aromaterapi lavender, dengan sifat antiseptik dan relaksasi, terbukti efektif menurunkan keparahan insomnia lansia. Presurvei di Desa Sukajaya Lempasing mengonfirmasi bahwa 70% lansia mengalami gangguan tidur, menegaskan kebutuhan intervensi terpadu untuk meningkatkan kualitas dan kuantitas tidur lansia. Tujuan: Memberikan gambaran mengenai asuhan keperawatan dengan intervensi aromaterapi lavender pada lansia yang mengalami gangguan pola tidur. Metode:  Kegiatan dilaksanakan pada 26 Juni–3 Juli 2025 di Desa Sukajaya Lempasing, Pesawaran, Lampung. Dua lansia dipilih sebagai responden berdasarkan kriteria inklusi dan eksklusi. Intervensi aromaterapi lavender diberikan selama tujuh hari dengan pendampingan keluarga, serta pertemuan tatap muka pada hari pertama dan kedelapan. Penelitian menggunakan desain one-group pre-test & post-test, data dikumpulkan melalui pengkajian, wawancara, dan observasi menggunakan lembar observasi dan Pittsburgh Sleep Quality Index (PSQI), serta dianalisis secara deskriptif untuk membandingkan skor sebelum dan sesudah intervensi. Hasil: Menunjukkan peningkatan kualitas tidur pada kedua responden setelah intervensi aromaterapi lavender, dengan penurunan skor gangguan tidur dari kategori buruk menjadi baik: Responden 1 dari skor 17 menjadi 7, dan Responden 2 dari skor 16 menjadi 6. Simpulan: Aromaterapi lavender selama tujuh hari terbukti efektif sebagai intervensi keperawatan mandiri nonfarmakologis, dengan hasil penurunan skor gangguan tidur lansia dari kategori buruk menjadi baik, peningkatan durasi tidur menjadi 6–7 jam per hari, serta perbaikan keluhan dan relaksasi. Saran: Aromaterapi lavender perlu diintegrasikan dalam praktik keperawatan lansia dengan gangguan tidur melalui edukasi relaksasi, pengelolaan lingkungan tidur, pemantauan berkala, dan keterlibatan keluarga untuk efektivitas jangka panjang.